Rhetorical Structure of Technical and Vocational Education and Training Video Lecture Introductions - Shamsudin, Sarimah; Izzat Rahim, Muhamad (Opción, 1970)
Considering the importance of rhetorical structure in listening tolectures, this study aims to investigate the rhetorical structure ofTechnical and Vocational Education and Training (TVET) video lectureintroductions. Five video lectures by Malaysian Polytechnics wereanalyzed using the ESP genre approach. The results show that TVETvideo lecture introduction commonly consists of two moves and threesteps. Additionally, it was found that the rhetorical structure forintroduction differs from one video lecture style to another. Inconclusion, TVET students can utilize the rhetorical structure of TVETvideo lecture introductions as a mental map in listening to video lectures